Mobilization of peripheral blood stem cells for autologous transplant in non-Hodgkin's lymphoma and multiple myeloma patients by plerixafor and G-CSF and detection of tumor cell mobilization by PCR in multiple myeloma patients - Frühauf, Stefan; Ehninger, G.; Hübel, K.; Topaly, Julian; Goldschmidt, Hartmut; Ho, Anthony Dick; Müller, S.; Moos, Marion; Badel, K.; Calandra, G. (Bone marrow transplantation, 2010)
This report describes the first investigational use of plerixafor in Europe and the determination of tumor cell mobilization by polymerase chain-reaction after plerixafor treatment in a subset of patients with multiple myeloma (MM). Thirty-five patients (31 MM and 4 NHL) received granulocyte colony-stimulating factor (G-CSF) (10 μg/kg) each morning for 4 days. Starting the evening of Day 4, patients recieved plerixafor 0.24 mg/kg. Apheresis was initiated 10-11 h later, in the morning of Day 5. This regimen of G-CSF treatment each morning before apheresis and plerixafor treatment in the evening was repeated for up to 5 consecutive days. Mobilization with plerixafor and G-CSF resulted in a median 2.6-fold increase in peripheral blood (PB) CD34+ cell count compared with before plerixafor treatment. All patients collected ⩾2 × 106 CD34+ cells/kg and 32 of 35 patients collected ⩾5 × 106 CD34+ cells/kg. After plerixafor treatment, 3 of 7 patients had a small increase and 4 of 7 patients had a small decrease in PB tumor cells. No G-CSF was given post transplant. The median number of days to polymorphonuclear leukocyte and platelet engraftment was 14.0 and 11.0, respectively. There were no reports of graft failure. Plerixafor was generally well tolerated. Mobilization of PB CD34+ cells was consistent with previous clinical trials. The addition of plerixafor did not significantly increase the relative number of PB MM tumor cells.
Published online 13 July 2009
Gesehen am 12.01.2022